Re-use : the art and politics of integration and anxiety - Hegewald, Julia A. B.; Mitra, Subrata Kumar, 1949- (SAGE India, 2012)
Presented here is a novel approach to understanding the relationship between the past and the present using the unique concept of re-use, wherein elements from the past are strategically adapted into the present, and thus become part of a new modernity. The book uses this method as a heuristic tool for analysing and interpreting cultural and political changes and the transnational flow of ideas, concepts and objects. The chapters apply this concept to South Asia but the concept of re-use and the method of its application are both general and amenable to cross-cultural and comparative analysis.